A Fe-g-C3N4@PAN nanofiber membrane with catalytic function, its preparation method and application
Patent Information
- Application Number
- CN202610824536.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-09
- Publication Date
- 2026-09-18
AI Technical Summary
但其应用面临根本性制约:(1)活性物种“短命”与“低效”并存:SO4-•、•OH等自由基在水相中半衰期仅纳秒至微秒级,极易被HCO3-、Cl-、天然有机质(NOM)等水体共存组分猝灭,导致其有效利用效率低于15%;(2)催化界面“失活”与“钝化”频发:悬浮态纳米催化剂在反应中易发生团聚、金属浸出、表面吸附饱和,导致活性位点不可逆掩蔽,循环5次后催化活性衰减超60%
[0015]In this invention, the successful introduction of Fe-g-C3N4 effectively improves the surface roughness and pore structure of the fiber, providing more active sites for pollutant adsorption and catalytic reactions. Significant electronic interactions exist between Fe2O3 and g-C3N4, as well as between the heterojunction and the PAN matrix, laying a key electronic structural foundation for enhancing the catalytic activity of the composite material.
Smart Images

Figure CN122769031A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanofiber membrane technology, and in particular to a Fe-g-C3N4@PAN nanofiber membrane with catalytic function, its preparation method and application. Background Technology
[0002] Current mainstream water treatment processes (such as activated sludge processes, ozone oxidation, and traditional membrane filtration) generally suffer from drawbacks such as low removal rates (<40%), easy generation of toxic intermediates, inability to achieve mineralization, and high operating costs when dealing with the aforementioned new pollutants. For example, bisphenol A (BPA) has been detected at concentrations of 0.1–5.2 μg / L in wastewater treatment plant effluents and exhibits strong estrogenic activity; sulfamethoxazole (SMX), a typical antibiotic, not only induces the accumulation of antibiotic resistance genes (ARGs), but its photolysis products also possess genotoxicity; perfluorooctanoic acid (PFOA), due to its extreme chemical stability, is known as a "permanent chemical" and is almost impossible to degrade using conventional processes. Therefore, developing novel water treatment functional materials that combine high selectivity, strong oxidizing properties, easy separation, and long-term stability has become a cutting-edge issue and a rigid requirement in the field of environmental science and technology.
[0003] Heterogeneous advanced oxidation technologies (AOPs) have attracted much attention due to their recyclable catalysts and high oxidant utilization. Among them, transition metal carbon-based materials (such as Fe / g-C3N4 and Co@CNT) have become a research hotspot because they combine Fenton-like catalytic activity with the conductivity of carbon materials. However, their application faces fundamental constraints: (1) The active species are both "short-lived" and "inefficient": SO4 - • OH radicals have half-lives of only nanoseconds to microseconds in aqueous phases, making them highly susceptible to being converted by HCO3-. - Cl - (1) Natural organic matter (NOM) and other coexisting components in water are quenched, resulting in an effective utilization efficiency of less than 15%; (2) Frequent “deactivation” and “passivation” of the catalytic interface: Suspended nanocatalysts are prone to agglomeration, metal leaching and surface adsorption saturation during the reaction, resulting in irreversible masking of active sites, and the catalytic activity decreases by more than 60% after 5 cycles. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of the prior art by proposing a Fe-g-C3N4@PAN nanofiber membrane with catalytic function, its preparation method, and its application.
[0005] The first objective of this invention is to provide a method for preparing Fe-g-C3N4@PAN nanofiber membranes with catalytic function, comprising the following steps: S1. After ultrasonic treatment in ethanol, g-C3N4 nanosheets and Fe2O3 nanoparticles were dried and calcined in a tube furnace under a nitrogen atmosphere to obtain carbon-based transition metal nanocatalyst Fe-g-C3N4. S2. Fiber membranes are prepared by coaxial electrospinning, wherein the shell layer solution is obtained by dissolving polyacrylonitrile powder in N,N-dimethylformamide solution and then adding Fe-g-C3N4 and stirring; the core layer solution is obtained by dissolving polyacrylonitrile powder and polyvinylpyrrolidone (PVP) powder in N,N-dimethylformamide solution. S3. The fiber membrane prepared in step S2 is calcined in air to obtain a Fe-g-C3N4@PAN nanofiber membrane with catalytic function.
[0006] Furthermore, the iron content in Fe-g-C3N4 is 5-10% by mass.
[0007] Further, in step S1, the sample is calcined at 400°C for 2 hours at a heating rate of 5°C / min.
[0008] Furthermore, the coaxial electrospinning conditions were set as follows: voltage of 12 kV, receiving device rotation speed of 200 r / min, core-shell flow rate ratio of 1:1, and distance between needle and receiver of 11 cm. The collected fiber membrane was then heated to 500 °C at a heating rate of 1 °C / min and held for 6 h.
[0009] Furthermore, in step S2, the amount of Fe-g-C3N4 added is 5%-20% of the shell solution.
[0010] Furthermore, the mass ratio of polyacrylonitrile to polyvinylpyrrolidone is 2:1.
[0011] Furthermore, the concentration of polyacrylonitrile is 12-15 wt%.
[0012] Furthermore, in step S3, the temperature is increased to 500°C at a heating rate of 1°C / min and calcined for 6 hours.
[0013] A second objective of this invention is to provide a Fe-g-C3N4@PAN nanofiber membrane with catalytic function prepared by the method described above.
[0014] A third objective of this invention is to provide an application of the Fe-g-C3N4@PAN nanofiber membrane with catalytic function as described above, which degrades bisphenol A through PMS activation.
[0015] In this invention, the successful introduction of Fe-g-C3N4 effectively improves the surface roughness and pore structure of the fiber, providing more active sites for pollutant adsorption and catalytic reactions. Significant electronic interactions exist between Fe2O3 and g-C3N4, as well as between the heterojunction and the PAN matrix, laying a key electronic structural foundation for enhancing the catalytic activity of the composite material.
[0016] The Fe-g-C3N4@PAN nanofiber membrane with catalytic function prepared by this invention has excellent catalytic activity and cycle stability. Attached Figure Description
[0017] Figure 1 (a) SEM image of Fe-g-C3N4; (b) XRD patterns of g-C3N4 and Fe-g-C3N4; Figure 2 EDS and TEM images of the Fe-g-C3N4@PAN nanofiber membrane prepared in Example 1; Figure 3 Infrared spectra of three samples prepared in Example 1: g-C3N4, Fe-g-C3N4, and Fe-g-C3N4@PAN; Figure 4 XPS image of the Fe-g-C3N4@PAN nanofiber membrane prepared in Example 1; Figure 5a The effect of Fe2O3 mass fraction on the catalytic performance of bisphenol A degradation; Figure 5b Effect of Fe-g-C3N4 loading on the catalytic performance of bisphenol A degradation; Figure 6a The effect of pH value on the catalytic degradation performance of Fe-g-C3N4@PAN; Figure 6b The effect of coexisting ions on the catalytic degradation performance of Fe-g-C3N4@PAN; Figure 7 Cyclic stability of Fe-g-C3N4@PAN catalytic degradation of bisphenol A; Figure 8 The performance of three composite membranes in catalytic degradation of bisphenol A and tetracycline hydrochloride. Detailed Implementation
[0018] The following are specific embodiments of the present invention, which are described in conjunction with the accompanying drawings. However, the present invention is not limited to these embodiments.
[0019] Example 1 Preparation of Fe-g-C3N4@PAN nanofiber membranes (1) Synthesis of Fe-g-C3N4 20 g of urea was placed in a covered porcelain crucible and calcined in air at 550°C for 2 hours at a heating rate of 2°C / min. After cooling to room temperature, bulk graphitic carbon nitride (g-C3N4) was obtained as the product. Then, to synthesize graphitic carbon nitride nanosheets (g-C3N4NS), the bulk g-C3N4 powder was further calcined in a furnace at 500°C for 2 hours at a heating rate of 5°C / min, and then naturally cooled to room temperature to obtain dispersed graphitic carbon nitride nanosheets. The g-C3N4 nanosheets and Fe2O3 nanoparticles were added to 50 mL of ethanol and sonicated for 15 min, then stirred at room temperature for 24 h until the solvent was completely dissolved. Subsequently, the remaining mixture was dried at 60°C for 1 hour and calcined in a tube furnace at 400°C for 2 hours under a nitrogen atmosphere at a heating rate of 5°C / min to obtain carbon-based transition metal nanocatalyst Fe-g-C3N4. The mass of g-C3N4 nanosheets and Fe2O3 nanoparticles was controlled so that the mass of iron in Fe-g-C3N4 was 3%, 5%, and 10%, respectively.
[0020] (2) Preparation of Fe-g-C3N4@PAN Fe-g-C3N4@PAN fiber membranes were prepared using coaxial electrospinning. First, the shell solution was prepared: 3.0 g of polyacrylonitrile (PAN) powder was dissolved in N,N-dimethylformamide (DMF) solution and mechanically stirred for 4 h. Then, Fe-g-C3N4 was added, and stirring continued for 3 h; finally, Fe-g-C3N4 was added again, and the mixture was magnetically stirred for 6 h. The core solution was prepared by dissolving 1.0 g of polyacrylonitrile (PAN) powder and 0.5 g of polyvinylpyrrolidone (PVP) powder in N,N-dimethylformamide (DMF) solution and magnetically stirring for 6 h.
[0021] Coaxial electrospinning conditions were set as follows: voltage 12 kV, receiver rotation speed 200 r / min, core-shell flow rate ratio 1:1, and distance between needle and receiver 11 cm. The collected Fe-g-C3N4@PAN fiber membrane was then heated to 500 °C at a heating rate of 1 °C / min and held for 6 h to obtain Fe-g-C3N4@PAN nanofiber membrane with catalytic function. The amount of Fe-g-C3N4 added was 5%, 10%, 15%, and 20% of the shell solution mass, respectively, denoted as 5%Fe-g-C3N4@PAN, 10%Fe-g-C3N4@PAN, 15%Fe-g-C3N4@PAN, and 20%Fe-g-C3N4@PAN.
[0022] Material characterization analysis a) Morphological structure and crystal phase analysis of Fe-g-C3N4.
[0023] In Example 1, Fe-g-C3N4 powder was successfully prepared using urea and Fe salt as raw materials via a two-step calcination method. Figure 1 As shown in Figure a, the scanning electron microscopy (SEM) characterization results clearly show that the sample's microstructure is a layered structure. The X-ray diffraction (XRD) results for the g-C3N4 and Fe-g-C3N4 samples are shown below. Figure 1 As shown in b, by Figure 1 As shown in b, both g-C3N4 and Fe-g-C3N4 samples have two characteristic diffraction peaks, with positions of 13.1° and 27.4°, consistent with the standard card (JCPDS 87-1526). This indicates that Fe-g-C3N4 still retains the typical (100) and (002) double peaks (13.1° and 27.4°) of g-C3N4, confirming that its basic layered covalent organic framework has not been destroyed and that Fe has not initiated a crystal phase transformation or generated an independent iron oxide impurity phase. Among them, the stronger diffraction peak at 27.4° corresponds to the (002) crystal plane of g-C3N4, which is a characteristic peak of interlayer stacking of conjugated aromatic compounds. The weaker diffraction peak at 13.1° corresponds to the (100) crystal plane of g-C3N4, which belongs to the graphite-like intralayer stacking, which is generally considered to be the stacking between N pores in polymers with 3-S-triazine structure as the basic unit. As Fe is doped into g-C3N4, the intensity of the diffraction peaks on the (100) and (002) planes gradually decreases. This is because, on the one hand, g-C3N4 interacts with Fe, causing its planar structure to become disordered, which in turn reduces the stacking order of g-C3N4 layers, thereby reducing the crystallinity of the (100) and (002) planes; on the other hand, Fe embeds itself into the triazine ring nitrogen vacancies or edge amino groups through coordination, disturbing the interlayer van der Waals force balance, causing a small slip or twist in the stacking period, reducing the coherent scattering length. At the same time, the introduction of Fe may induce local electron redistribution, weakening the degree of overlap of interlayer electron clouds, and further weakening the (002) diffraction intensity.
[0024] b) Morphological and structural analysis of Fe-g-C3N4@PAN electrospinning.
[0025] Figure 2 These are EDS and TEM images of the Fe-g-C3N4@PAN nanofiber membrane prepared in Example 1, as shown. Figure 2The data shows that C, N, Fe, and O are uniformly distributed on the surface of PAN nanofibers, confirming that the Fe-g-C3N4 structure has been successfully and uniformly loaded onto the outer layer of the coaxial electrospinning, forming a good composite structure. The 0.270 nm lattice spacing clearly visible in the high-resolution transmission electron microscope (HR-TEM) image corresponds to the (104) crystal plane of α-Fe2O3, indicating that Fe2O3 has good crystallinity and forms a tight heterogeneous interface with g-C3N4. This interfacial contact enhances the interaction between the two components, thereby improving the catalytic activity of the composite material. The coaxial electrospinning technology constructs a unique core-shell structure. This design not only enriches the catalytically active components (Fe2O3 / g-C3N4) mainly on the fiber surface (shell layer), exposing the reactive sites, but also utilizes the PAN core layer to provide excellent mechanical strength and flexibility. This structure effectively prevents the aggregation and detachment of nanocatalysts, greatly improving the structural stability and recycling convenience of the material, and solving the bottleneck problem of the difficulty in recycling powdered catalysts.
[0026] Table 1 Physical structure of catalyst
[0027] Table 1 shows that with the increase of Fe-g-C3N4 heterojunction loading, the specific surface area (SSA) of the composite fiber membrane significantly increased from 14.25 m² / g for pure PAN to 18.58 m² / g (15% loading), and the total pore volume also increased significantly from 0.202 cm³ / g to 0.469 cm³ / g (20% loading). This indicates that the successful introduction of the catalyst effectively improved the surface roughness and pore structure of the fiber, providing more active sites for pollutant adsorption and catalytic reactions. Notably, the 15% loading sample exhibited the largest average pore size (4.75 nm), while the pore size decreased slightly at 20% loading (4.03 nm). This may be because excessive catalyst loading led to partial pore blockage or densification of the fiber surface, which is detrimental to mass transfer. Therefore, a 15% loading achieved a better balance between specific surface area, pore volume, and pore size, which is beneficial for constructing a membrane reactor with efficient mass transfer and high catalytic activity.
[0028] Figure 3 Infrared spectra of three samples prepared in Example 1—g-C3N4, Fe-g-C3N4, and Fe-g-C3N4@PAN—are shown to analyze the chemical structure and interactions of the composite materials. In the g-C3N4 spectrum, at 800 cm⁻¹... - The strong peak at ¹ is attributed to the out-of-plane bending vibration of the triazine ring, 1200–1650 cm⁻¹ -The multiple peaks within the range ¹ correspond to the stretching vibrations of C=N and C–N, indicating its typical graphitic carbon nitride structure. In the Fe-g-C3N4 spectrum, the aforementioned characteristic peaks still exist, but some peak positions have slightly shifted or their intensities have changed, suggesting that the introduction of Fe species may have coordinated with the N atoms in g-C3N4, affecting its electronic structure. In the Fe-g-C3N4@PAN spectrum, in addition to retaining the characteristic peaks of g-C3N4, typical absorption peaks of PAN also appear, such as at 2240 cm⁻¹. - The C≡N stretching vibration peak at ¹ and 2900 cm⁻¹ - The C–H stretching vibration peaks near ¹ and the overall spectrum confirm that the Fe-g-C3N4 heterojunction was successfully loaded onto PAN fibers and that the structure is stable.
[0029] Figure 4 XPS images of Fe-g-C3N4@PAN electrospun fibers. X-ray photoelectron spectroscopy (XPS) analysis further revealed the chemical state and interaction between the Fe-g-C3N4 heterojunction and the PAN matrix. Full spectrum (a) clearly shows the presence of C, N, O, and Fe in the Fe-g-C3N4@PAN composite material, directly confirming that the heterojunction catalyst was successfully loaded onto the PAN fiber surface. In the N1s high-resolution spectrum, both pure g-C3N4 (Figure b) and Fe-g-C3N4 (Figure c) exhibit two main characteristic peaks at 398.7 eV and 400.2 eV, respectively, corresponding to the sp² hybridized nitrogen atom (C=NC) in the triazine ring and the tertiary nitrogen atom (N-(C)3) connecting the triazine ring. This indicates that the introduction of Fe did not disrupt the core framework structure of g-C3N4. In the N1s spectrum (Figure d) of the Fe-g-C3N4@PAN composite material, in addition to the two characteristic peaks originating from g-C3N4 mentioned above, a new peak at 401.5 eV, attributed to the cyano group (-C≡N) in PAN, appears, providing strong evidence for the presence of the PAN matrix. Compared to pure g-C3N4, the binding energy of the C=NC peak in Fe-g-C3N4@PAN shows a slight positive shift. This shift suggests significant electronic interactions between Fe2O3 and g-C3N4, as well as between the heterojunction and the PAN matrix. This interaction facilitates the construction of an internal electric field, promoting the effective separation and migration of photogenerated electron-hole pairs, thus laying a crucial electronic structural foundation for enhancing the catalytic activity of the composite material.
[0030] To compare the results, two combined strategies, blending spinning and vacuum filtration, were then used to analyze the dispersion uniformity and interfacial contact state of Fe-g-C3N4@PAN.
[0031] Comparative Example 1 Blending spinning method: The spinning solution is pre-mixed by direct blending, with Fe-g-C3N4 and PAN in a mass ratio of 1:10, a total spinning solution concentration of 10wt%, and a spinning voltage of 18kV.
[0032] Comparative Example 2 Vacuum filtration method: Continuous vacuum filtration allows a uniformly dispersed suspension (Fe-g-C3N4 to PAN mass ratio 1:10) to pass through a prepared PAN fiber membrane. As the number of filtration cycles increases, the amount of Fe-g-C3N4 on the membrane surface gradually increases.
[0033] Catalytic oxidation performance and mechanism of Fe-g-C3N4@PAN Catalytic performance study The activity of coaxially spun Fe-g-C3N4@PAN in degrading bisphenol A (BPA) via persulfate (PMS) activation was measured. Figure 5a shows the regulatory effect of Fe2O3 mass fraction (3%, 5%, and 10% relative to the mass of Fe-g-C3N4) on BPA degradation efficiency. When the Fe2O3 content was 3%, the degradation rate was only 20.6%, indicating that insufficient active sites limited the PMS activation ability; as the Fe2O3 content increased to 5%, the degradation rate jumped to 78.9%, which was attributed to Fe²⁺. + / Fe³ + The cycle accelerated the PMS decomposition, producing more SO4· - The degradation rate further increases to 96.2% when the Fe2O3 content reaches 10%, at which point the active sites tend to be saturated and the catalytic efficiency approaches its peak. It is worth noting that excessive Fe2O3 content may lead to particle agglomeration, which will reduce the effective specific surface area. Considering economic factors, 10% is the optimal Fe2O3 loading, balancing the density of active sites and the dispersibility of the material.
[0034] Figure 5b reveals the relationship between the loading of Fe-g-C3N4 catalyst (5%, 10%, 15%, 20%) and the degradation rate of the endocrine disruptor bisphenol A (BPA). At a loading of 5%, the degradation rate was only 61.7%, indicating insufficient catalyst leading to a scarcity of active sites. As the loading increased to 10%, the degradation rate rose to 80.3%, attributed to the synergistic effect of the π-π conjugated structure of g-C3N4 and Fe2O3 enhancing PMS activation. At a loading of 15%, the degradation rate reached a peak of 96.8%. However, when the loading increased to 20%, the degradation rate decreased to 85.6%, presumably because excessively high catalyst concentrations caused particle agglomeration, clogging membrane pores and shortening the contact time between pollutants and active sites. Therefore, 15% is the optimal catalyst loading, balancing active site density and membrane structure stability.
[0035] The activity of the Fe-g-C3N4@PAN catalytic membrane in degrading bisphenol A via PMS activation was further investigated. Figure 6a The effect of initial solution pH (4–10) on BPA degradation efficiency was demonstrated. Experimental results showed that the catalytic system exhibited a significant pH dependence, showing a trend of "increasing first and then decreasing." Under acidic conditions (pH=4), the degradation rate was 75.9%, reaching a peak of 98.3% as the pH increased to weakly alkaline (pH=8). This indicates that in a neutral to weakly alkaline environment, PMS molecules are more easily activated by the active sites on the catalyst surface, and the dissolution and precipitation of Fe species reach an optimal balance, which is conducive to the generation of free radicals. However, when the pH was further increased to 10, the degradation rate dropped back to 78.6%, possibly due to excessively high OH- ions. - While concentration can stimulate PMS to generate free radicals, it also leads to the self-quenching effect of free radicals or changes the charge properties on the catalyst surface, hindering the adsorption of reactants.
[0036] Figure 6b Further investigation was conducted into common inorganic anions (NO3) in actual water bodies. 3- Cl - Ca 2+ Na + The study investigated the interference of different ions on BPA degradation. The results showed that the presence of different ions had varying degrees of inhibitory effects on the catalytic system. Among them, NO... 3- and Ca 2+ The impact on degradation efficiency is relatively small, indicating that the system has good tolerance to nitrates and hardness ions. In contrast, Cl... - and Na + The presence of Cl led to a decrease in activity, especially Cl. - As a typical free radical quencher, it readily reacts with •SO4. - The reaction with •OH generates chlorine free radicals with weak oxidizing power, thereby hindering the degradation pathway of BPA.
[0037] The cyclic stability of Fe-g-C3N4@PAN catalytic degradation of bisphenol A was further investigated. Figure 7 As shown, after five repeated uses, the Fe-g-C3N4@PAN catalytic membrane still achieved a 93.3% removal rate of bisphenol A, with only a 4.5% decrease, demonstrating good stability.
[0038] Finally, this study compared the degradation performance of three composite membranes with different structures designed in the original study on two substrates: bisphenol A and tetracycline hydrochloride.
[0039] like Figure 8As shown, the coaxial spun membrane exhibited the highest degradation rates for bisphenol A and tetracycline hydrochloride, reaching 98.5% and 95.3%, respectively. This indicates that the multi-level gradient structure constructed by coaxial spinning technology can achieve a gradient distribution of Fe-g-C3N4 within or on the surface of the fiber at the microscale. This multi-level structure not only increases the specific surface area but also provides abundant mass transfer channels, enabling substrate molecules to diffuse more efficiently to the active sites. Compared to filtration membranes (prone to clogging and catalyst detachment) and blended membranes (with uneven catalyst dispersion and agglomeration), the coaxial structure firmly "encapsulates" the catalyst within the fiber matrix, preventing the loss of active components while ensuring their surface accessibility.
[0040] For any points not covered above, existing technologies shall apply.
[0041] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a Fe-g-C3N4@PAN nanofiber membrane with catalytic function, characterized in that, Includes the following steps: S1. After ultrasonic treatment in ethanol, g-C3N4 nanosheets and Fe2O3 nanoparticles were dried and calcined in a tube furnace under a nitrogen atmosphere to obtain carbon-based transition metal nanocatalyst Fe-g-C3N4. S2. Fiber membranes are prepared by coaxial electrospinning, wherein the shell layer solution is obtained by dissolving polyacrylonitrile powder in N,N-dimethylformamide solution and then adding Fe-g-C3N4 and stirring; the core layer solution is obtained by dissolving polyacrylonitrile powder and polyvinylpyrrolidone (PVP) powder in N,N-dimethylformamide solution. S3. The fiber membrane prepared in step S2 is calcined in air to obtain a Fe-g-C3N4@PAN nanofiber membrane with catalytic function.
2. The preparation method according to claim 1, characterized in that, The iron content in Fe-g-C3N4 is 5-10% by mass.
3. The preparation method according to claim 1, characterized in that, In step S1, calcination is carried out at 400°C for 2 hours at a heating rate of 5°C / min.
4. The preparation method according to claim 1, characterized in that, Coaxial electrospinning conditions were set as follows: voltage 12 kV, receiver rotation speed 200 r / min, core-shell flow rate ratio 1:1, and distance between needle and receiver 11 cm. The collected fiber membrane was then heated to 500 °C at a heating rate of 1 °C / min and held for 6 h.
5. The preparation method according to claim 1, characterized in that, In step S2, the amount of Fe-g-C3N4 added is 5%-20% of the shell solution.
6. The preparation method according to claim 1, characterized in that, The mass ratio of polyacrylonitrile to polyvinylpyrrolidone is 2:
1.
7. The preparation method according to claim 1, characterized in that, The concentration of polyacrylonitrile is 12-15 wt%.
8. The preparation method according to claim 1, characterized in that, In step S3, the temperature is increased to 500℃ at a heating rate of 1°C / min and calcined for 6 h.
9. A Fe-g-C3N4@PAN nanofiber membrane with catalytic function prepared by the preparation method according to any one of claims 1-8.
10. An application of the Fe-g-C3N4@PAN nanofiber membrane with catalytic function as described in claim 9, characterized in that, Bisphenol A was degraded by PMS activation.